Comportamento estratégico de micro e pequenas empresas paulistas de base tecnológica - Musetti, Tiago Fernando (Universidade Federal de São Carlos, 2020)
This thesis aims to identify the main characteristics of strategic behavior in micro and small technology-bases firms. In the present competitive scenario, even more dynamic and uncertain, innovation can be a source of competitive advantage and economic growth. Technology-based firms innovate trying to remain competitive in the markets where they operate and the dynamic capabilities can help the development of innovation strategies in dynamic sectors. The research method in this thesis was made of two phases: the first one had a survey, whose results were analyzed using techniques such as: main components, factorial analysis, cluster analysis and multiple correspondence analysis. In the second phase, a study of five cases was carried out, containing information collected via semi structured interviews by means of content analysis. The multiple correspondence analysis showed that micro and small technology-based firms which have a Research and Development (R&D) department and carried out radical and/or incremental innovations during the years 2015 to 2017, were founded from researches conducted in universities. Besides analyses correlation indicated that increases in investment taxes in R&D resulted in proportional raises in annual revenues of micro and small technology-based firms. The multiple case studies showed that micro and small technology-based firms tend to launch and improve processes, products and/or services, using technology resources, market research, R&D investments, employees, updating capability and costumer partnerships. Regarding the dynamic capability formation process, this theses observed that the detection micro foundation is influenced by the development of reliable strategic partnerships with extern agents, specially by the costumer; the mobilization micro foundation is influenced by technological development to explore market opportunities and meet costumer’s needs; and the reconfiguration micro foundation is influenced by external factors, such as partnership with costumers and internal factors, such as technological development. Finally, it was possible to identify evidence from micro and small technology-based firms which put and effort into their formation of dynamic capabilities, defined innovation and competitive strategies, invested on R&D their innovative performance by means of launching and improvement of processes, products and/or services.
Strategic behavior of micro and small technology-based firms located in state of Sao Paulo
Keywords: Capacidades dinâmicas; Estratégia de inovação; Vantagem competitiva; Micro e pequena empresa de base tecnológica; Dynamic capabilities; Innovation strategy; Competitive advantage; Micro and small technology-based firms; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::PLANEJAMENTO EM CIENCIA E TECNOLOGIA